Changes in zooplankton communities in Kazan city waterbodies after remediation activities - Derevenskaya O.Yu. (Трансформация экосистем)
In 2019–2020, remediation activities in the Komsomolsky pond and Lake Maryino were carried out in the Kazan city (Volga River, Russia). During these works, bottom sediments were extracted using the Geotube® technology, submerged macrophytes were removed, and the coastal zone was developed. Water aerators were additionally installed in Lake Maryino. In both waterbodies, a decrease in their trophic status was observed after the activities performed. The zooplankton diversity in the Komsomolsky pond increased from 30 to 48 species, rotifers and cladocerans prevailed. In Lake Maryino, the number of species increased from 41 to 52, rotifers prevailed. After the activities were completed, frequent changes in the dominant zooplankton species and dominating of a single species were observed during the first year. In subsequent years, two or three species dominated. The lowest abundance and biomass were registered during the remediation period; these indicators have increased in subsequent years. During the remediation period and immediately after it, the greatest variability of zooplankton abundance and biomass throughout the vegetation period was noted. Over time, the fluctuation range has decreased, and the communities became more stable. No obligate predators were found in zooplankton trophic chains of Lake Maryino; in the Komsomolsky pond, they were registered singly, without making a significant contribution to the energy transformation. Cladocerans and rotifers contributed the most to the energy flows. After the remediation activities, the production of zooplankton communities increased.